2004
DOI: 10.1583/03-1143.1
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Studies of the Anaconda Stent-Graft and Observations of Nitinol Corrosion Resistance

Abstract: This Anaconda stent-graft has demonstrated its ability to exclude arterial aneurysms. The device used in this study was an experimental prototype, and the manufacturer has incorporated new immobilization features into the model for clinical use. The constituent materials appear to be suitable in terms of biocompatibility, biofunctionality, and short-term durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…These are different values from those measured in canine animal trial reported by Guidoin et al [6]. They measured the fabric count of Anaconda sample after 1 month and 3 months' implantation, the warp count increased after the implantation, whereas the weft count decreased significantly after 1 month implantation, then it increased slightly but still below the value of the control sample.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…These are different values from those measured in canine animal trial reported by Guidoin et al [6]. They measured the fabric count of Anaconda sample after 1 month and 3 months' implantation, the warp count increased after the implantation, whereas the weft count decreased significantly after 1 month implantation, then it increased slightly but still below the value of the control sample.…”
Section: Resultscontrasting
confidence: 73%
“…Considering that leakage of the endovascular devices is a severe problem, water permeability should be the most important fatigue performance to be considered in this study. However, the authors think that changes in fabric count, porosity, as well as diameter are also very important because these parameters are always considered by researchers from medical field [6]. So the changes in water permeability, fabric radial and longitudinal count, bursting strength, porosity and tubular diameter during the experiments were selected to characterize the fatigue performance of the prototype samples.…”
Section: Characterization Of Fatigue Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The Anaconda uses a particularly thin Dacron (0.15 vs.~0.35 mm), and the porosity of all existing grafts are approximately the same, at 65%, 59 with the incidence of Type IV endoleak being fairly high peri-operatively (this is known as 'contrast blushing').…”
Section: Type IVmentioning
confidence: 99%
“…In animal models, endothelialization of the stent graft seems to occur quickly (within 3 months) and along the whole length of the graft. 59,122 Although there are occasional reports of this occurring in humans, 106 it is thought that endothelialization does not commonly take place. 87 Therefore, further work on developing methods to encourage endothelialization should be performed, so that the stent graft becomes integrated with the body.…”
Section: Limb Occlusionmentioning
confidence: 99%